2003
DOI: 10.1002/jid.1025
|View full text |Cite
|
Sign up to set email alerts
|

More on the effectiveness of public spending on health care and education: a covariance structure model

Abstract: Using data for a sample of developing countries and transition economies, this paper estimates the relationship between government spending on health care and education and selected social indicators. Unlike previous studies, where social indicators are used as proxies for the unobservable health and education status of the population, this paper estimates a latent variable model. The findings suggest that public spending is an important determinant of social outcomes, particularly in the education sector. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 19 publications
14
92
0
12
Order By: Relevance
“…The results were obtained after controlling for consumption and literacy levels. The findings reported from 111 developing and transition countries by Baldacci et al (2002) also support the argument that public health spending is effective in improving health status. A similar study by Issa and Ouattara (2005) found that health expenditure reduces infant mortality.…”
Section: Empirical Studiessupporting
confidence: 55%
“…The results were obtained after controlling for consumption and literacy levels. The findings reported from 111 developing and transition countries by Baldacci et al (2002) also support the argument that public health spending is effective in improving health status. A similar study by Issa and Ouattara (2005) found that health expenditure reduces infant mortality.…”
Section: Empirical Studiessupporting
confidence: 55%
“…Studies by Anand and Ravallion (1993) and Psacharopoulos and Patrinos (2002) support a positive correlation between public social spending and education and health outcomes. Baldacci et al (2003) come to the same conclusion, with education outlays showing up as a stronger determinant of social indicators than health expenditure. On the other hand, a number of studies find no significant relationship between public spending on education and education outcomes Tan 1992, 1998) or between health outlays and health status (Filmer et al 1998).…”
Section: Social Spending Human Capital and Economic Growthmentioning
confidence: 68%
“…Similarly, Baldacci et al (2003) provide evidence that social spending is an important determinant of social outcomes, particularly in the education sector.…”
Section: Social Spending and Aggregate Welfarementioning
confidence: 97%
“…15 Income is one of the crucial determinants of health status (Pritchett and Summers 1996). A number of studies also show that higher levels of female education are associated with better health status of children as well as the population in general ( 2008), we include the share of female students in primary and secondary schools as an indicator for gender equality, which takes account of the institutional factors that may have signi…cant bearing on child health through female education.…”
mentioning
confidence: 99%